2016
DOI: 10.1073/pnas.1615540113
|View full text |Cite
|
Sign up to set email alerts
|

Control of embryonic stem cell self-renewal and differentiation via coordinated alternative splicing and translation of YY2

Abstract: Translational control of gene expression plays a key role during the early phases of embryonic development. Here we describe a transcriptional regulator of mouse embryonic stem cells (mESCs), Yin-yang 2 (YY2), that is controlled by the translation inhibitors, Eukaryotic initiation factor 4E-binding proteins (4E-BPs). YY2 plays a critical role in regulating mESC functions through control of key pluripotency factors, including Octamer-binding protein 4 (Oct4) and Estrogen-related receptor-β (Esrrb). Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 72 publications
5
76
1
Order By: Relevance
“…The appearance of YY2 may be due to the fact that the C-terminal binding domains of YY1 and YY2 are highly conserved. Indeed, ChIP-seq derived binding peaks of YY2 contained the YY1 motif at peak centers, indicating that YY2 binds similar regions and that there is an overlap of genes regulated by both TFs [45,46].…”
Section: Results On the Extended Feature Spacementioning
confidence: 99%
“…The appearance of YY2 may be due to the fact that the C-terminal binding domains of YY1 and YY2 are highly conserved. Indeed, ChIP-seq derived binding peaks of YY2 contained the YY1 motif at peak centers, indicating that YY2 binds similar regions and that there is an overlap of genes regulated by both TFs [45,46].…”
Section: Results On the Extended Feature Spacementioning
confidence: 99%
“…It harbors 5 miRNAs: Has-miR-550a-3p, Has-miR-335-3p, Has-miR-571, Has-miR-377-3p, Has-miR-105-5p. Interestingly, a huge literature argues that several mRNA targets work in important phases of embryo development: SOCS and FOX targets are spatio-temporally regulated in the endometrium, reflecting the acquisition of receptivity, maternal recognition of pregnancy and implantation [288,289]; YY2 is one of the major regulators of mouse embryonic stem cell self-renewal and lineage commitment [290] as well as the RNA methyltransferases NSUN4 is enriched in mouse tissues during embryo development [291]. Interestingly, NANOS1 has an essential role in the central nervous system development [292].…”
Section: Spz-dependent Cernet Involved In Germ Cell Progression and Ementioning
confidence: 99%
“…Although the role of YY1 in cardiomyocyte differentiation, cardiac development, and cardiomyopathy has been previously explored (Sucharov et al, 2003;Morikawa et al, 2013;Beketaev et al, 2015), studies of the involvement of YY2 in cardiovascular development and diseases have been limited, albeit that YY2 expression was detected in mouse hearts during both embryogenesis and postnatal stages (Drews et al, 2009). In a more recent study, it was revealed that the expression of YY2 induced by doxycycline promoted the differentiation of mouse embryonic stem cells into cardiovascular lineages (Tahmasebi et al, 2016), indicating an important role for YY2 in cardiac lineage commitment. In the present study, we found that the expression of YY2 induced by a-MHC-Cre, which was activated at ∼E9.0, caused partial prenatal lethality (i.e., after E16.5).…”
Section: Yy2 and Cardiomyopathymentioning
confidence: 99%
“…Our microarray analysis further confirmed that cell cycle genes were dysregulated in E14.5 dTg mouse hearts, as evidenced by the decreased pH3 staining in dTg hearts compared with control hearts. Given that YY2 depletion mediated by CRISPR/Cas9 caused peri-implantation lethality (Tahmasebi et al, 2016), we believe that YY2 plays a critical role in cell death and proliferation and that the level of YY2 should be tightly controlled during embryogenesis. Intriguingly, we did not observe any discernible cell cycle progression defect or increased apoptosis in CRISPR/Cas9-mediated YY2 knockout Hela cells.…”
Section: Yy2 and Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation